Punch sleeve
Patent Information
- Application Number
- JP2026518644
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-29
- Filing Date
- 2024-08-27
- Publication Date
- 2026-10-14
Smart Images

Figure 2026534290000001_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present invention relates to a punch sleeve, a punch device, the use of the punch sleeve, and a method for drawing a metal blank into a can body. BACKGROUND ART
[0002] European Patent Application Publication No. 2746413 discloses a punch for the production of metal beverage cans. PRIOR ART DOCUMENTS PATENT DOCUMENTS
[0003] PATENT DOCUMENT 1 European Patent Application Publication No. 2746413 SUMMARY OF THE INVENTION PROBLEMS TO BE SOLVED BY THE INVENTION
[0004] A typical process for manufacturing beverage cans usually starts with cutting a circular metal blank from a metal sheet usually made of aluminum alloy or steel. Next, the metal blank is usually placed in a drawing press, where the blank is drawn into the shape of a cup. Thereafter, the punch sleeve mounted on the ram, which thereby forms the punch, is rapidly pressed against the cup-shaped metal blank at that point, usually within less than one second, and usually continuously, normally through a drawing die and usually a plurality of ironing dies. The cup-shaped metal blank is deep drawn in this way, that is, its diameter is reduced and its height is increased, and then it is ironed, that is, its height is further increased mainly by stretching and thinning the cup wall, and a beverage can body is produced. These two steps are usually referred to as drawing and ironing.
[0005] An object of the present invention is to provide a punch sleeve that can improve productivity during the production of beverage cans and reduce downtime and energy consumption. MEANS FOR SOLVING THE PROBLEMS
[0006] This object is achieved by the punch sleeve according to claim 1. Advantageous embodiments of the present invention are disclosed in the dependent claims, which may be freely combined with each other and with claim 1, and are also disclosed in further embodiments of the present disclosure including the accompanying Figure 1 and Figure 2 and the corresponding descriptions thereof. Mode for Carrying Out the Invention
[0007] The punch sleeve is made of a sintered material comprising the following components: 10 to 35 weight percent of tungsten carbide, a total of 50 to 60 weight percent of one or more selected from titanium carbide, titanium carbonitride, and titanium nitride, a total of 5 to 35 weight percent of one or more selected from cobalt and nickel, 0 to 1.5 weight percent of chromium, 0 to 2.5 weight percent of molybdenum, and a total of 0 to 1 weight percent of other additives, wherein the sum of the weight percentages of the aforementioned components is 95 to 100 weight percent.
[0008] The term "weight percent" and the like, unless otherwise stated, should be understood throughout the present disclosure as the weight percent of any of the aforementioned components, and optionally further components of the sintered material, relative to the total weight of the sintered material.
[0009] With respect to the components of the sintered material, the total S1 (tungsten carbide + titanium carbide + titanium carbonitride + titanium nitride) in weight percent may be in the range of 60 to 95 weight percent, the total S2 (cobalt + nickel) in weight percent may be in the range of 5 to 35 weight percent, and the total S3 (chromium + molybdenum + other additives) may be in the range of 0 to 5 weight percent, such that the total S = S1 + S2 + S3 may be in the range of 95 to 100 weight percent; here, when the sintered material consists of the aforementioned components, this is possible and contemplated, and S is 100 weight percent.
[0010] "The sum of one or more selected from titanium carbide, titanium carbonitride, and titanium nitride" should be understood, unless otherwise stated, as long as these components are present, the sum of the weight percentages of the titanium carbide, titanium carbonitride, and titanium nitride is calculated, and at least one (titanium carbide, titanium nitride, titanium carbonitride), two (titanium carbide and titanium nitride, titanium carbide and titanium carbonitride, titanium nitride and titanium carbonitride), or all three (titanium carbide, titanium carbonitride, and titanium nitride) of these components are present in the sintered material in the weight percentages disclosed herein.
[0011] It is possible and conceivable that the sintered material is substantially or completely free of titanium nitride, that is, that the titanium carbide and / or titanium carbonitride exist substantially without titanium nitride, or without titanium nitride, respectively. Therefore, with respect to the definition of the composition of the sintered material, "the sum of one or more selected from titanium carbide, titanium carbonitride, and titanium nitride" is subsequently replaced with "the sum of one or more selected from titanium carbide and titanium carbonitride."
[0012] "Total of one or more selected from cobalt and nickel" should be understood, unless otherwise stated, as long as the cobalt and nickel are present, the total weight percentage of the cobalt and nickel is calculated, and one (cobalt, nickel) or both (cobalt and nickel) are present in the sintered material in the weight percentages disclosed herein.
[0013] The term “other additives” should be understood throughout this disclosure, unless otherwise stated, in reference to the industrial-scale manufacturing process of the sintered material, and these “other additives” mean, for example, the use of recycled raw materials, green body pressing and sintering, unavoidable impurities, and / or those introduced to achieve certain properties.
[0014] Because the punch sleeve is sleeve-shaped, it can be attached to the ram by sliding it, preferably by a nut screwed onto the threaded portion of the ram. In this case, the nut abuts against the shoulder portion of the punch sleeve facing axially forward, with a radial gap between the nut and the punch sleeve. Therefore, the punch sleeve is a hollow, open-end body, preferably open at both ends. The punch sleeve may be a one-piece body or a body made of two or more parts. The punch sleeve helps to distribute the force more evenly and is easier to replace and maintain than a one-piece ram used directly for punching.
[0015] The punch sleeve is made from a sintered material containing the following components: 10-35 weight percent tungsten carbide, 50-60 weight percent total of one or more selected from titanium carbide, titanium carbonitride, and titanium nitride, 35-5 weight percent total of one or more selected from cobalt and nickel, 1.5-0 weight percent chromium, 2.5-0 weight percent molybdenum, and 1-0 weight percent of other additives, where the total weight percentage of the above components is 95-100 weight percent; thereby achieving an optimal balance between lightness, wear resistance, and toughness. In other words, the optimal balance between titanium carbide, titanium nitride, and / or titanium carbonitride for lightness and tungsten carbide for wear resistance has been found in combination with an optimal binder content formed by the cobalt and / or nickel for improved toughness; the titanium carbide, titanium nitride, and / or titanium carbonitride each have an average weight of approximately 5 g / cm³. 3 It has a relatively low mass density, while the mass density of tungsten carbide is approximately 15.6 g / cm³. 3 Therefore, it is heavier on a volume basis; the present invention is not bound by any special characteristics related to the precise calculation of these densities.
[0016] The aforementioned weight reduction is achieved by a relatively large total content of titanium carbide, titanium nitride, and / or titanium carbonitride, which have relatively low mass densities. This is made possible at least by the presence of the relatively heavy tungsten carbide and cobalt and / or nickel, which improve the toughness. The weight reduction achieved by the composition of the sintered material allows the punch sleeve to reduce stress on the entire punch-die system, extend the lifespan of the die and other parts of related equipment, and reduce operating costs because less energy is required to move the punch sleeve. This is particularly advantageous for the manufacturing of mass-produced beverage cans. Furthermore, the punch sleeve can improve accuracy during punching and improve worker safety because it is lighter and easier to handle.
[0017] Compared to tungsten carbide, which has a higher mass density, titanium carbide, titanium nitride, and / or titanium carbonitride have relatively low mass densities, i.e., high specific volumes. Therefore, depending on the components present, the sintered material has a microstructure mainly formed by crystal grains consisting of titanium carbide, titanium nitride, and / or titanium carbonitride.
[0018] Tungsten carbide typically has a stoichiometric composition of WC. Titanium carbide, when present, is typically (Ti 1-r ,W r ) has a stoichiometric composition of C, where r is in the range of 0 to less than 0.5, preferably 0 to 0.15, that is, some tungsten may be present in the titanium carbide. When present, titanium carbonitride is usually (Ti 1-x ,W x )(C 1-y ,N y ) has a stoichiometric composition, where x is in the range of 0 to less than 0.5, preferably 0 to 0.15, and y is in the range of greater than 0 and less than 1, i.e., some tungsten may be present in the titanium carbonitride. When present, titanium nitride usually has a stoichiometric composition of TiN.
[0019] When titanium carbide and titanium carbonitride are selected from among titanium carbide, titanium carbonitride and titanium nitride, the titanium carbide is titanium carbonitride containing a portion of tungsten, i.e., Ti 1-x ,W x )(C 1-y ,N y ) can exist as substantially pure titanium carbide, i.e., TiC(r=0). Here, x is greater than 0 and less than 0.5, preferably greater than 0 and 0.15 or less, and y is greater than 0 and less than 1. Therefore, when titanium carbide and titanium carbonitride are both present in these stoichiometric compositions, individual "titanium carbide crystal grains" and "titanium carbonitride crystal grains" can usually be distinguished by EBSD (electron backscatter diffraction) images in the microstructure of the sintered material. In this case, the "titanium carbide crystal grains" usually appear as substantially black particles, and the "titanium carbonitride crystal grains" usually appear as lighter gray shades, having an average size larger than that of the "titanium carbide crystal grains".
[0020] The source of molybdenum, when present, can usually be molybdenum powder and / or molybdenum carbide powder added to the powder mixture that can be pressed and sintered to produce the sintered material.
[0021] The source of chromium, when present, can usually be chromium powder and / or chromium carbide powder added to the powder mixture that can be pressed and sintered to produce the sintered material.
[0022] Preferably, the sintered material consists of the following components: 10 to 35 weight percent tungsten carbide, 50 to 60 weight percent in total of one or more selected from titanium carbide, titanium carbonitride, and titanium nitride, 5 to 35 weight percent in total of one or more selected from cobalt and nickel, 0 to 1.5 weight percent chromium, 0 to 2.5 weight percent molybdenum, and 0 to 1 weight percent in total of other additives, wherein the sum of the weight percentages of the aforementioned components is 100 weight percent. Preferably, the sintered material consists of the following components: 10-35 weight percent tungsten carbide, 50-60 weight percent in total of one or more selected from titanium carbide, titanium carbonitride, and titanium nitride, and 35-5 weight percent in total of cobalt and nickel, where the cobalt content is greater than 0 weight percent, the nickel content is greater than 0 weight percent, 1.5-0 weight percent chromium, 2.5-0 weight percent molybdenum, and 1-0 weight percent of other additives, where the total weight percentage of the above components is 100 weight percent. Thus, the composition of the sintered material subsequently includes cobalt and nickel.
[0023] Preferably, the sintered material consists of the following components: 10-35 weight percent tungsten carbide, 50-60 weight percent in total of one or more selected from titanium carbide and titanium carbonitride, 35-5 weight percent in total of one or more selected from cobalt and nickel, 1.5-0 weight percent chromium, 2.5-0 weight percent molybdenum, and 1-0 weight percent of other additives, where the total weight percentage of the components is 100 weight percent. Therefore, the composition of the sintered material does not contain titanium nitride but contains cobalt and nickel.
[0024] According to further embodiments of the punch sleeve, the total content of one or more selected from titanium carbide, titanium carbonitride, and titanium nitride is 52 to 56 weight percent. In this disclosure, in which the sintered material contains or consists of the above components, it has been found that the tool life of the punch sleeve is improved, including when the composition of the sintered material does not contain titanium nitride, within this narrower range of titanium carbide, titanium carbonitride, and titanium nitride, which can be used to replace any of the broader range of titanium carbide, titanium carbonitride, and / or titanium nitride.
[0025] According to a further embodiment of the punch sleeve, the tungsten carbide content is 27 to 33 weight percent. In this disclosure, where the sintered material contains or consists of the above components, it has been found that tool life of the punch sleeve is improved within this narrower range of tungsten carbide, including when the composition of the sintered material does not contain titanium nitride, which can be used to replace any of the broader range of tungsten carbide.
[0026] According to a further embodiment of the punch sleeve, the nickel content is 1 to 6 weight percent. In the present disclosure, where the sintered material contains or consists of the above components, it has been found that the tool life of the punch sleeve is improved when the nickel content is in the range of 1 to 6 weight percent, which can be used to replace any of the broader range of nickel, including when the composition of the sintered material does not contain titanium nitride. Nickel has been found to at least improve corrosion resistance.
[0027] According to a further embodiment of the punch sleeve, the nickel content is 2 to 4 weight percent. In the present disclosure, where the sintered material contains or consists of the above components, it has been found that the tool life of the punch sleeve is improved when the nickel content is in a narrower range of 2 to 4 weight percent, which can be used to replace any of the broader range of nickel, including when the composition of the sintered material does not contain titanium nitride.
[0028] According to further embodiments of the punch sleeve, the chromium content is 0.3 to 1.5 weight percent, preferably 0.5 to 1.3 weight percent. In this narrower range of chromium, which can be used to replace any of the broader range of chromium in the present disclosure in which the sintered material contains or consists of the above components, it has been found that the tool life of the punch sleeve is improved, including when the composition of the sintered material does not contain titanium nitride. It has been found that chromium reduces the average grain size of at least tungsten carbide.
[0029] According to further embodiments of the punch sleeve, the molybdenum content is 0.5 to 2.5 weight percent. In this disclosure, where the sintered material contains or consists of the above components, it has been found that within this narrower range of molybdenum, which can be used to replace any of the broader range of molybdenum, the tool life of the punch sleeve is improved, including when the composition of the sintered material does not contain titanium nitride. Molybdenum has been found to increase the resistance to thermal deformation.
[0030] According to a further embodiment of the punch sleeve, titanium carbonitride has a stoichiometric composition (Ti 1-x ,W x )(C 1-y ,N y ) has such that x is greater than 0 and up to 0.15, and y is greater than 0 and less than 1. A stoichiometric composition (Ti) where x is greater than 0 and up to 0.15, and y is greater than 0 and less than 1. 1-x ,W x )(C 1-y ,N y It has been found that ) improves the wear resistance achieved by the titanium carbonitride. This is because a relatively small amount of tungsten W (x is limited to 0.15 or less) is present in the titanium carbonitride, improving wear resistance without making the titanium carbonitride too heavy, i.e., without impairing the weight reduction achievable by the titanium carbonitride. Titanium carbonitride has a stoichiometric composition (Ti) where x is greater than 0 and up to 0.15, and y is greater than 0 and less than 1. 1-x ,W x )(C 1-y ,N y It was found that when the titanium carbide has a stoichiometric composition of TiC, i.e., substantially pure titanium carbide, the wear resistance is further improved.
[0031] According to a further embodiment of the punch sleeve, the tungsten carbide has an average grain size in the range of 0.2 μm to 3 μm, preferably 1 μm to 3 μm. It has been found that when the average grain size of the tungsten carbide is in the range of 0.2 μm to 3 μm, preferably 1 μm to 3 μm, the tool life of the punch sleeve is improved.
[0032] The average grain size of the tungsten carbide particles shall be measured as the "linear section length" in accordance with the international standard ISO 4499-2:2008(E), unless otherwise specified. EBSD (electron backscatter diffraction) images of sintered samples shall be used as the basis unless otherwise specified. The measurement method for such micrographs is described, for example, in KP Mingard et al., "Comparison of EBSD and conventional methods of grain size measurement of hard metals", Int. Journal of Refractory Metals & Hard Materials 27 (2009) 213-223, unless otherwise specified.
[0033] In a further embodiment, the punch sleeve has a nose located at one end of the punch sleeve, a trailing edge located at a second end of the punch sleeve opposite to the nose, and a cylindrical portion between the nose and the trailing edge. The nose is preferably rounded to allow for a smooth initial contact with the metal blank during the drawing process.
[0034] In a further embodiment, the punch sleeve has an internal contact shoulder on a portion of the nose. The contact shoulder is typically formed by a smaller diameter section of the punch sleeve, located between a relatively large inner diameter portion located on the second end side of the punch sleeve and a relatively large inner diameter portion located on the nose side outside the section. The contact shoulder is designed for contact with a fastening element, which is typically screwed into the threaded portion of the ram. Here, the ram is typically slid into the section such that the threaded portion of the ram protrudes from the section on a portion of the nose, and that the fastening element contacts the shoulder section when screwed into the threaded portion.
[0035] The objective can also be solved by the punching device according to claim 13.
[0036] The punching device comprises a ram and a punch sleeve according to any of the related claims including claim 1, and / or an embodiment including the attached Figures 1 and 2 and their corresponding descriptions, wherein the punch sleeve is slidably mounted on the ram. The advantages of the punching device are the same as those disclosed for the punch sleeve. The punch sleeve allows the ram to reciprocate faster, improves alignment, reduces energy consumption, and extends the lifespan of the device, as the moving weight is reduced and wear resistance and toughness are improved. The device may also comprise one or more dies designed to allow the punch sleeve to move through the dies, thereby enabling deep drawing of a metal blank into a can body.
[0037] The objective can also be achieved by using the punch sleeve according to claim 14.
[0038] A metal blank can be drawn into a can body using a punch sleeve according to any of the related claims, including claim 1, and / or an embodiment including the attached Figures 1 and 2 and their corresponding descriptions. The advantages of this use are the same as those disclosed for the punch sleeve.
[0039] The objective can also be solved by a method of drawing a metal blank according to claim 15 into a can body.
[0040] The process for forming a can body from a metal blank involves the following steps: a) A step of providing a punch sleeve according to an embodiment including any related claim including claim 1, and / or attached Figures 1 and 2 and their corresponding descriptions, or a step of providing a punching device according to an embodiment including any related claim including claim 13, and / or attached Figures 1 and 2 and their corresponding descriptions, b) A process of providing a metal blank, c) A process in which the punch sleeve from process a) and the metal blank from process b) are moved relative to each other, thereby drawing the metal blank from process b) into the can body. This includes, preferably, a metal blank that has already been drawn into a cup-shaped body and is provided in that manner in step b). Typically, one or more dies are provided in step c), and a punch sleeve moves through the dies in a continuous stroke, drawing each metal blank or cup-shaped can body. [Brief explanation of the drawing]
[0041] [Figure 1] A schematic diagram of the vertical cross-section of a punch sleeve. [Figure 2] A schematic diagram of the vertical cross-section of a punching device.
[0042] Figure 1 shows a punch sleeve 1 in a longitudinal section along the longitudinal axis 2, and the punch sleeve 1 is capable of reciprocating motion along the longitudinal axis 2.
[0043] Punch sleeve 1 is a one-piece body made from a sintered material consisting of the following components: 53.5 weight percent of titanium carbide and titanium carbonitride combined, 30 weight percent of tungsten carbide, 12 weight percent of cobalt, 3 weight percent of nickel, and 1.5 weight percent of chromium. The sum of the above components is 100 weight percent, and the sum of cobalt and nickel is 15 weight percent.
[0044] The content of the aforementioned components may be selected differently according to corresponding embodiments of the present disclosure, and / or the sintered material may contain one or more further components selected from molybdenum and other additives according to corresponding embodiments of the present disclosure, so that the total weight percentage of the components may be 100 weight percent.
[0045] Tungsten carbide grains have an average grain size of 2.3 μm, which is representative of the average grain size ranges of 0.2 μm to 3 μm and 1 μm to 3 μm. The average grain size of these tungsten carbide grains is measured as the "linear section length" according to the international standard ISO 4499-2:2008(E). EBSD (electron backscatter diffraction) micrographs of sintered samples are used as the basis. The measurement method for such micrographs is described, for example, in KP Mingard et al., "Comparison of EBSD and conventional methods of grain size measurement of hard metals," Int. Journal of Refractory Metals & Hard Materials 27 (2009) 213-223.
[0046] The punch sleeve 1 is designed to draw a metal blank into a can body by a single stroke along a direction 3 parallel to the longitudinal axis 2, and is rotationally symmetric with respect to the longitudinal axis 2. The punch sleeve 1 has a nose 4 located at one end and a trailing edge 5 located at a second end opposite to the nose 4. The nose 4 is rounded and designed for initial contact with the metal blank. The punch sleeve 1 further has a cylindrical section 6 between the nose 4 and the trailing edge 5, which is connected to a tapered rear section 7 that tapers from the outer diameter D1 of the cylindrical section 6 to a smaller diameter closer to the trailing edge 5.
[0047] The punch sleeve 1 further has an inner contact shoulder portion 9a on its outer surface 8, inner surface 9, and part of the nose 4. The contact shoulder portion 9a has a surface that is perpendicular to the longitudinal axis 2 and faces toward the nose 4.
[0048] The contact shoulder portion 9a is designed to contact a fastening element that axially secures the punch sleeve 1 to the ram, which will be further discussed in the description of Figure 2.
[0049] The punch sleeve has an overall length L1 measured parallel to the longitudinal axis 2, from the nose 4 to the trailing edge 5. The overall length L1 is 184 mm as an example, but may also be in the range of 180 mm to 190 mm, or any other length, however 180 mm to 190 mm is preferred for the manufacture of so-called sleek cans, where drawing with a lightweight and wear-resistant sleeve is particularly advantageous.
[0050] The rear section 7 has a length L2, which is measured similarly to length L1. L2 is 12.4 mm as an example, but may be in the range of 10 mm to 15 mm, or any other length, although 10 mm to 15 mm is preferred for the drawing of so-called sleek cans.
[0051] The cylindrical portion 6 has a length L3, which is measured in the same way as length L1. Length L3 is 164.6 mm as an example, but may also be in the range of 160 mm to 170 mm, or any other length, although 160 mm to 170 mm is preferred for the drawing process of so-called sleek cans.
[0052] The punch sleeve 1 has an inner diameter D2 closer to the nose 4 and a smaller inner diameter D3 located behind the contact shoulder 9a. D2 is 41 mm as an example, but may also be in the range of 35 mm to 45 mm or any other diameter, however 35 mm to 45 mm is preferred for drawing so-called sleek cans. D3 is 37 mm as an example, but may also be in the range of 35 mm to 40 mm or any other value, as long as D3 is smaller than D2. D1 is 57 mm as an example, but may also be in the range of 55 mm to 60 mm or any other value, however 55 mm to 60 mm is preferred for drawing so-called sleek cans.
[0053] The punch sleeve 1 further has an inner diameter D4 in a portion of the tip section 7, which is equal to the inner diameter D3. D3 and D4 are designed to fit the outer diameter of the ram that is inserted into the punch sleeve 1 and contacts the inner surface 9, which defines the inner diameters D3 and D4.
[0054] Figure 2 shows a longitudinal cross-sectional view of the same punch sleeve 1 as in Figure 1. In Figure 2, the punch sleeve 1 is mounted to the ram 10 by sliding. The punching device 11 comprises the punch sleeve 1 and the ram 10. The ram 10 is a cylindrical body made of steel, rotationally symmetric with respect to its longitudinal axis 2, and is fixed axially by a fastening element, a nut 14, which engages with the threaded portion of the ram 10. As is clear from comparing Figures 1 and 2, the nut 14 abuts against the contact shoulder 9a. The nut 14 has radial clearance with respect to the inner surface 9, which allows the nut 14 to be screwed into the ram 10.
[0055] Figure 2 further shows a metal blank 12 that has already been drawn into a cup shape by a cupping press, having an inner diameter D4 greater than the diameter D1, and further having a wall thickness D5 and a height L4 measured in the same way as the length L1. D4 is 83 mm as an example, but can also be selected from different diameters suitable for interaction with the punch sleeve 1. L4 is 37 mm as an example, but can also be selected from different heights suitable for interaction with the punch sleeve 1.
[0056] With the use of the punch sleeve 1 and the punching device 11, the metal blank 12 is drawn into the ring die 13 by the stroke of the punch sleeve 1 against the metal blank 12, and it is also possible and conceivable to have multiple ring dies, each positioned below the die 13.
[0057] This stroke reduces the diameter D4 of the metal blank 12 to a diameter smaller than the diameter D1, and increases the height L4, for example, by more than 1.5 times.
[0058] According to the method of drawing a metal blank 12 into a can body, the following steps are performed: a) a punch sleeve 1 or punching device 11 is provided, b) a metal blank 12 is provided, and c) the metal blank 12 is drawn by pressing the punch sleeve 1 and the metal blank 12 against each other, in which case the punch sleeve 1 is moved into a die 13.
[0059] The punch sleeve 1, and by extension the punching device 12, are lightweight and wear-resistant, resulting in a longer lifespan, lower energy consumption, and less maintenance required when drawing metal blanks into can bodies. This lightweight nature is primarily due to the sintered material containing a total of 50-60 weight percent titanium carbide and titanium carbonitride, one or more examples of which are selected from titanium carbide, titanium carbonitride, and titanium nitride, as well as a relatively low tungsten carbide content of 10-35 weight percent to improve wear resistance and a cobalt and nickel binder content of 35-5 weight percent to improve toughness.
[0060] The present invention is not limited to the design of the punch sleeve 1. In other embodiments, the dimensions of the punch sleeve 1, particularly dimensions L1, L2, L3, D1, D2, and D3, can be modified relative and / or absolute to take into account a desired can body design and / or a different design of ram 10.
[0061] [Examples] The reference punch sleeve, hereafter referred to as punch sleeve A, was made from a sintered material consisting of the following components: 88 weight percent tungsten carbide and 12 weight percent cobalt. The sintered material of punch sleeve A has a density of approximately 14.3 g / cm³. 3 It had a density of [value].
[0062] A further reference punch sleeve, hereafter referred to as punch sleeve B, was made from a sintered material consisting of the following components: a total of 38 weight percent titanium carbide, 30 weight percent tungsten carbide, 24 weight percent cobalt, 6 weight percent nickel, and 2 weight percent chromium. The sintered material of punch sleeve B had a density of approximately 8.0 g / cm³. 3 It had a density of [value].
[0063] The punch sleeve according to the present invention, hereinafter referred to as "Punch Sleeve Inv.", is made from a sintered material consisting of the following components: 53.5 weight percent titanium carbide, 30 weight percent tungsten carbide, 12 weight percent cobalt, 3 weight percent nickel, and 1.5 weight percent chromium. The sintered material of Punch Sleeve Inv. has a density of approximately 7.0 g / cm³. 3 It had a density of [value].
[0064] Five samples were taken from each of punch sleeves A, B, and Inv. and subjected to the same wear test to determine sliding wear under linear reciprocating ball-on-sample contact in terms of wear mark depth. ASTM G133-22 (Standard Test Method for Linear Reciprocating Ball-on-Flat Sliding Wear, published 2022) can be used as a reference for conducting such wear tests. In each sintered material, one wear mark was produced under the same pressing force and surface conditions until a predetermined number of ball-on-sample reciprocating motions were reached. The average wear mark depth was calculated from the five samples.
[0065] These and further abrasion test results for further compositions based on the sintered material of punch sleeve Inv. are discussed in relative terms in the following sections of the disclosure, which should be sufficient for those skilled in the art to reproduce and confirm the identified trends and effects. Those skilled in the art know how to conduct abrasion tests on sintered materials and, naturally, use the same test parameters when comparing the abrasion behavior of different sintered materials.
[0066] The sintered material of punch sleeve A showed the deepest wear marks. The sintered material of punch sleeve B showed wear marks that were 13% shallower (less deep) compared to the wear marks of punch sleeve A. The sintered material of punch sleeve Inv. showed wear marks that were 21% shallower (less deep) compared to the wear marks of punch sleeve A, and 9% shallower (less deep) compared to the wear marks of punch sleeve B.
[0067] Therefore, the following trend was identified: The combination of 53.5 weight percent titanium carbide and 30 weight percent tungsten carbide in the sintered material of punch sleeve Inv. not only results in a significantly lighter punch sleeve, but also provides superior wear resistance compared to the presence of 88 weight percent tungsten carbide without titanium carbide, as in the case of the sintered material of punch sleeve A, which has more than twice the density.
[0068] The combination of 53.5% by weight titanium carbide and 30% by weight tungsten carbide in the sintered material of punch sleeve Inv. not only results in an even lighter punch sleeve, but also provides superior wear resistance compared to the lower titanium carbide content of 38% combined with the same 30% by weight tungsten content, as in the case of the sintered material of punch sleeve B.
[0069] As a result, in the method for drawing a metal blank 12, it was found that the punch sleeve of the present invention not only extends tool life due to its improved wear resistance, but also requires less energy to move due to its low density.
[0070] Further similar wear tests were conducted on additional sintered materials for punch sleeves (hereinafter referred to as "additional sintered materials," unless otherwise specified). The composition of the additional sintered materials for punch sleeves is based on the composition of the sintered material from which punch sleeve Inv. was fabricated, but with systematic variations in one or more components each time.
[0071] Further sintering of titanium carbide in the material was found to improve wear resistance compared to being outside this range, with a range of 52 to 56 weight percent. To this end, the total S1 = (tungsten carbide + titanium carbide) in weight percent was kept constant at 83 weight percent, and the combined nickel and cobalt content was kept constant at 17 weight percent, resulting in a total of 100 weight percent.
[0072] Further sintering of the material was found to improve wear resistance by ranging from 5 to 35 weight percent of combined nickel and cobalt compared to outside this range. To this end, the combined content of tungsten carbide and titanium carbide was appropriately adjusted within 65 to 95 weight percent to reach 100 weight percent.
[0073] Further sintering was found to improve wear resistance by ranging the nickel content from 1 to 4 weight percent compared to outside this range. To this end, the combined nickel and cobalt content was kept constant at 15 weight percent, and the combined titanium carbide and tungsten carbide content was kept constant at 85 weight percent, resulting in a total of 100 weight percent.
[0074] It was found that the presence of additional chromium in the further sintered material, when in the range of 0.3 to 1.5 weight percent, improved wear resistance compared to when it was outside this range. To this end, the total content of titanium carbide and tungsten carbide was kept constant at 85 weight percent with 53 weight percent titanium carbide, and the total content of nickel and cobalt was adjusted as appropriate to 100 weight percent.
[0075] It was found that the presence of molybdenum in the sintered material in the range of 0.5 to 2.5 wt% improved wear resistance compared to when it was outside this range. In this case, the total content of titanium carbide and tungsten carbide was kept constant at 85 wt% with 53 wt% titanium carbide, and the total content of nickel and cobalt was adjusted as appropriate to 100 wt%. The presence of other additives up to 1% by weight was found to be acceptable for punch sleeve applications.
[0076] It was found that an average particle size of tungsten carbide in the range of 1 μm to 3 μm improved wear resistance compared to when it was outside this range. Sintered material from Punch Sleeve Inv. was used in this study. This trend was confirmed for any further sintered material.
[0077] In the sintered material for the punch sleeve Inv., titanium carbide and titanium carbonitride were selected from among titanium carbide, titanium carbonitride, and titanium nitride. A further prepared sintered material having the same composition as the sintered material for the punch sleeve Inv., in which only titanium carbide is selected from among titanium carbide, titanium carbonitride, and titanium nitride, or in which only titanium nitride is selected from among titanium carbide, titanium carbonitride, and titanium nitride, It has been found that the presence of both titanium carbide and titanium carbonitride improves wear resistance. In particular, when the titanium carbide is essentially pure, i.e., TiC, and the titanium carbonitride contains some tungsten, i.e., (Ti 0.85 ,W 0.15 )(C 0.8 ,N 0.2 ), (Ti 0.90 ,W 0.10 )(C 0.8 ,N 0.2 ), (Ti 0.95 ,W 0.05 )(C 0.8 ,N 0.2 ), (Ti 0.85 ,W 0.15 )(C 0.5 ,N 0.5 ), (Ti 0.90 ,W 0.10 )(C 0.5 ,N 0.5 ), (Ti 0.95 ,W 0.05 )(C 0.5 ,N 0.5 ), (Ti 0.85 ,W 0.15 )(C 0.2 ,N 0.8 ), (Ti 0.90 ,W 0.10 )(C 0.2 ,N 0.8 ), (Ti 0.95 ,W 0.05 )(C 0.2 ,N 0.8 It was found that abrasion resistance is improved when the following is present:
[0078] In a further prepared sintered material having the same composition as the punch sleeve Inv., only titanium carbide was selected from titanium carbide, titanium carbonitride, and titanium nitride.
[0079] In a further prepared sintered material having the same composition as the punch sleeve Inv., only titanium carbonitride was selected from titanium carbide, titanium carbonitride, and titanium nitride.
[0080] In a further prepared sintered material having the same composition as the punch sleeve Inv., only titanium nitride was selected from titanium carbide, titanium carbonitride, and titanium nitride.
[0081] In a further prepared sintered material having the same composition as the punch sleeve Inv., titanium carbide and titanium nitride were selected from titanium carbide, titanium carbonitride, and titanium nitride.
[0082] In a further prepared sintered material having the same composition as the punch sleeve Inv., titanium carbonitride and titanium nitride were selected from titanium carbide, titanium carbonitride, and titanium nitride.
[0083] In the further prepared sintered material having the same composition as the punch sleeve Inv., titanium carbide, titanium carbonitride, and titanium nitride were selected from titanium carbide, titanium carbonitride, and titanium nitride.
Claims
1. The following ingredients: Tungsten carbide 10-35% by weight, One or more selected from titanium carbide, titanium carbonitride, and titanium nitride, totaling 50-60% by weight. One or more elements selected from cobalt and nickel, totaling 35-5% by weight. Chromium 1.5-0% by weight, Molybdenum 2.5-0% by weight, Other additives totaling 1-0% by weight, Includes, A punch sleeve (1) made from a sintered material in which the total weight percentage of the aforementioned components is 95 to 100% by weight.
2. The total content of one or more substances selected from titanium carbide, titanium carbonitride, and titanium nitride is 52 to 56% by weight. The punch sleeve (1) according to claim 1.
3. The tungsten carbide content is 27-33% by weight. A punch sleeve (1) according to any of the preceding claims.
4. The nickel content is 1 to 6% by weight. A punch sleeve (1) according to any of the preceding claims.
5. The nickel content is 2-4% by weight. The punch sleeve (1) according to claim 4.
6. The chromium content is 0.3 to 1.5% by weight. A punch sleeve (1) according to any of the preceding claims.
7. The molybdenum content is 0.5 to 2.5% by weight. A punch sleeve (1) according to any of the preceding claims.
8. Titanium carbonitride is (Ti 1-x , W x ) (C 1-y , N y It has the stoichiometric composition of ), where x is greater than 0 and up to 0.15, and y is greater than 0 and less than 1. A punch sleeve (1) according to any of the preceding claims.
9. Tungsten carbide has an average crystal grain size in the range of 0.2 μm to 3 μm. A punch sleeve (1) according to any of the preceding claims.
10. Tungsten carbide has an average crystal grain size in the range of 1 μm to 3 μm. The punch sleeve (1) according to claim 9.
11. A nose (4) is positioned at one end of the punch sleeve (1), On the opposite side of the nose (4), the trailing edge (5) is located at the second end of the punch sleeve (1), The cylindrical portion (6) between the nose (4) and the trailing edge (5), A punch sleeve (1) according to any of the preceding claims, comprising:
12. The punch sleeve (1) has an internal contact shoulder portion (9a) in part of the nose (4), The punch sleeve (1) according to claim 11.
13. The device comprises a ram (10) and a punch sleeve (1) as described in any of the preceding claims, wherein the punch sleeve (1) is slidably mounted on the ram (10). Punching device (11).
14. Use of the punch sleeve (1) according to any one of claims 1 to 12 for drawing a metal blank (12) into a can body.
15. A method for forming a can body from a metal blank (12), comprising the following steps: a) A step of providing a punch sleeve (1) according to any one of claims 1 to 12 or a punching device according to claim 13, b) A step of providing a metal blank (12), c) A step in which the punch sleeve (1) from step a) and the metal blank (12) from step b) are moved relative to each other, thereby forming the metal blank (12) from step b) into a can body. Methods that include...
Citation Information
Patent Citations
Cemented carbide punch
EP2746413A1